Rictor maintains endothelial integrity under shear stress - Li, Hui; Zhou, Wen-Ying; Liu, Yi-Xian; Xia, Yi-Yuan; Xia, Chun-Lei; Pan, Dao-Rong; Li, Zheng; Shi, Yi; Chen, Shao-Liang; Zhang, Jun-Xia (Frontiers in Cell and Developmental Biology, 2022)
Background: Endothelial injury instigated by low shear stress (LSS) is an initiating factor in the pathogenesis of various cardiovascular diseases, including atherosclerosis, hypertension, and thrombotic diseases. LSS activated the mammalian target of rapamycin complex2 (mTORC2) signaling pathway. Rictor, the main constituent protein of mTORC2, is involved in vascular development. However, it is unclear about the impact of conditional Rictor ablation on endothelial homeostasis, especially on endothelial specific markers as vascular endothelial-cadherin (VE-cadherin) and von Willebrand factor (VWF) under blood flow stimulation. Objective: We aimed to investigate whether endothelial Rictor is involved in maintaining vascular endothelial integrity and the potential role of Rictor in atheroprone blood flow mediated endothelial injury. Methods and results: Immunofluorescence staining showed endothelial Rictor was successfully knockout in mouse model. Scanning electron microscopy (EM) detection revealed disruption of the endothelial monolayer in the thoracic aorta of Rictor-deficient mice. Furthermore, Scanning EM and transmission EM showed that Rictor deletion disrupted endothelial integrity and expanded cell junctions in the LCA region. In vitro, LSS induced the polarity disorder of actin filaments and the endocytosis of VE-cadherin, the key component of adherens junctions (AJs) in human umbilical vein endothelial cells. After Rictor downregulation by small interfering RNA, the endocytosis of VE-cadherin and stress fibers increased. Knockdown Rictor inhibited LSS-induced VWF upregulation, and downregulation of VE-cadherin decreased LSS-induced VWF expression, suggesting that VE-cadherin/VWF is a possible mechanism mediated by Rictor in the pathological process of LSS-induced endothelial injury. Conclusion: Rictor is a key protein regulating endothelial integrity under vascular physiological homeostasis, and Rictor mediated LSS-induced endothelial injury by regulating AJs and VWF.